COMMERCIAL CARCASS PIECES OF FEMALE BALI DUCKS AGED 26 WEEKS GIVEN FEED CONTAIN FERMENTATION PAPAYA LEAF MEAL - I P. E., Astika; Siti, N. W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
This research aims to assess the weight of commercial carcass pieces female bali ducks aged 26 weeks were given feed containing fermented papaya leaf meal, which was held in cages owned by Mr. I Ketut Sunatra located at roadway Bingin Nambe, Kediri, Tabanan, for 14 weeks. The experiment designd used was Completely Randomized Design (CRD) with three treatments, namely treatments P0 (Ration without fermented papaya leaf meal as controls), P1 (Ration contain of 8% fermented papaya leaf meal), and P2 (Ration contain of 16% fermented papaya leaf meal), treatment consists of three replications and each replication using two female bali ducks aged 12 weeks with an average initial weight range of 1286.23 ± 92.88 g. The variables observed were weight and percentage commercial carcasspieces of chest, thigh, drumstick, wings and backs. The results showed that the use of ration containing 8% and 16% fermented papaya leaf meal is statistically not significant (P>0.05) on commercial carcass pieces. The weight of commercial carcass pieceswere increased ondrumstick, wings and backs on the treatment P1, but statistically not significant different (P>0.05). Based on the results of this research, it can be concluded that administration of fermented papaya leaf meal at level of 8% and 16% had no effect on commercial carcass of female bali ducks.  Keywords: fermented papaya leaf, femalebali ducks, commercial carcass.